The Potential for High‑tech Exports from Selected EU Member States to China and the Related Opportunities Arising from the Belt and Road Initiative - Kittová, Zuzana; Družbacká, Barbora (Comparative Economic Research. Central and Eastern Europe, 2024)
The EU’s economic relations with China are characterised by a significant trade deficit. Enhancing EU exports of high-tech products, in particular, to China is the best way out of this imbalance. In doing so, EU countries can take advantage of the opportunities provided by the Belt and Road Initiative (BRI) that intends to improve connectivity between Europe and Asia. Objective: This study aims to identify the untapped potential for high-tech exports of selected EU countries in trade with China and to evaluate the opportunities arising from the BRI in utilising this potential. Research Design & Methods: To assess the overall high-tech export potential of selected EU countries to China, the export gap was calculated using the concept of revealed comparative advantages. Findings: Among the examined EU countries, Hungary and the Czech Republic were found to have the greatest high-tech export growth potential to China. The largest export gaps were recorded in electrical machinery and equipment. Implications & Recommendations: The findings of the study can be used by European businesses to adjust their export strategies. It can also be used by government institutions of the studied countries when designing their economic and trade policies, particularly vis-à-vis China and the BRI initiative, within the field of supporting infrastructure projects, as well as high-tech industries. Contribution & Value Added: The study contributes to the literature on the potential of EU export growth to China that has not been sufficiently explored yet. The novelty of the study is in identifying specific high-tech commodities with the highest potential for export to China.